Evaluating Data-Driven Stories & Storytelling Tools - Amini, Fereshteh; Brehmer, Matthew; Bolduan, Gordon; Elmer, Christina; Wiederkehr, Benjamin (Data-Driven Storytelling, 2018)
This chapter provides a review of how DDSs and the tools used to produce them are evaluated. Evaluation is a far-reaching concept; among the topics discussed in this chapter include the evaluation of a DDS in a newsroom context as well as the evaluation of novel storytelling tools and techniques in academic research settings. The discussion spans a diverse set of goals, acknowledging the different perspectives of storytellers. publishers, readers, tool builders, and researchers. It also reviews possible criteria for assessing whether these goals are met, as well as evaluation methods and metrics that address these criteria. This chapter is intended to serve as a guide for those considering whether and how they should evaluate the stories they produce or storytelling tools or techniques that they develop.